Pretransplant Hepatitis C Virus Treatment Decreases Access to High-quality Livers. Issue 4 (April 2021) - Strauss, Alexandra T.; Ishaque, Tanveen; Weeks, Sharon; Hamilton, James P.; Simsek, Cem; Durand, Christine M.; Massie, Allan B.; Segev, Dorry L.; Gurakar, Ahmet; Garonzik-Wang, Jacqueline M.
Abstract : Background: Despite the revolutionary role of direct-acting antivirals for hepatitis C virus (HCV), the treatment timing for liver transplant candidates remains controversial. We hypothesize that deferring treatment until after liver transplantation improves access to a larger and higher-quality donor pool without a detrimental impact on post-liver transplantation outcomes. Methods: This single-center study includes recipients that underwent deceased-donor liver transplant with HCV as the primary indication January 1, 2014, to December 31, 2018. For recipients that were untreated (n = 87) versus treated (n = 42) pre-LT, we compared post-LT mortality using Cox regression with inverse probability of treatment-weighted data. Results: Among pre-LT untreated recipients, 95% were willing to accept an HCV+ donor, and 44.8% received a positive HCV antibody and nucleic acid amplification test (NAT) liver. Among pre-LT treated recipients, 5% were willing to accept an HCV+ donor, and 100% received a negative HCV antibody and NAT liver. The median calculated model for end-stage liver disease at transplant was similar between pre-LT untreated (13, IQR = 9–22) and treated recipients (11, IQR = 8–14) ( P  = 0.1). Pre-LT treated recipients received livers from older (47 y old versus 37, P  < 0.01) and higher body mass index donors (30.2 versus 26.6; P  = 0.04) and spent longer on the waiting list (319 d 180, P  < 0.001). Unadjusted post-LT mortality at 1 year was higher in the pre-LT treated recipients (14.6% versus 3.5%, P  = 0.02). After adjusting for recipient factors, pre-LT treated recipients trended toward a 3.9 times higher risk of mortality compared with the pre-LT untreated recipients (adjusted hazard ratio = 0.97 3.8615.4 ) ( P  = 0.06). Conclusions: Deferring HCV treatment improves access to higher-quality donors and may improve post-LT survival.